Постать Володимира Вернадського в роботах українських дослідників - Ємець, Т.М. (Українська біографістика, 2010)
The work sums up the achievements of Ukrainian scientists in describing the life and activity of V.I. Vernadsky in the context of social, political and cultural life of Ukraine and development of Ukrainian science. It analyses new approaches and trends in studying the ties of V.I. Vernadsky with Ukraine.